Teachers’ Strategy in Teaching V - Novri Susanti Suparman (STAI Nurul Falah Airmolek, 2021)
Nowadays, English vocabulary has been taught since the first grade of elementary schools. It shows that one of the crucial aspects of English is vocabulary. Vocabulary as one of the language component is very important in language skills namely writing, reading, listening, and speaking. It will be very difficult to master these four basic language skills without sufficient words. Mastery of words is very important in language learning. If we listen, we listen to words, if we speak we speak or use words, if we read, we encounter words, if we write we use words. Considering the importance of words, teachers have to find ways to teach words or vocabulary. It is known that vocabulary plays an important role in learning a new language. In teaching vocabulary, teachers should be creative in implementing strategies in order to motivate students to learn. So, the writer was going to investigate the teachers’ strategies in teaching vocabulary at SDN 102 Pekanbaru and what are the considerations that make the teachers apply certain strategies in teaching vocabulary.